Implications of the Intestinal Microbiota in Diagnosing the Progression of Diabetes and the Presence of Cardiovascular Complications - Alina Mihaela Leustean; Manuela Ciocoiu; Anca Sava; Claudia Florida Costea; Mariana Floria; Claudia Cristina Tarniceriu; Daniela Maria Tanase (Journal of Diabetes Research)
The prevalence of diabetes is steadily rising, and once it occurs, it can cause multiple complications with a negative impact on the whole organism. Complications of diabetes may be macrovascular: such as stroke and ischemic heart disease as well as peripheral vascular and microvascular diseases—retinopathy, nephropathy, and neuropathy. Key factors that cause cardiovascular disease in people with diabetes include hyperglycemia, dyslipidemia, obesity, insulin resistance, inflammation, hypertension, autonomic dysfunction, and decreased vascular response capacity. Microbes can be considered a complex endocrine system capable of ensuring the proper functioning of the body but are also responsible for the development of numerous pathologies (diabetes, coronary syndromes, peripheral arterial disease, neoplasia, Alzheimer’s disease, and hepatic steatosis). Changes in the intestinal microbiota may influence the host’s sensitivity to insulin, body weight, and lipid and carbohydrate metabolism. Dysbiosis causes activation of proinflammatory mechanisms, metabolic toxicity, and insulin resistance. Trimethylamine N-oxide (TMAO) is a microbial organic compound generated by the large intestine, and its concentration increases in the blood after ingestion of foods rich in L-carnitine and choline, such as red meat, eggs, and fish. The interest for TMAO in cardiometabolic research has recently emerged, given the preclinical evidence that reveals a link between TMAO, diabetes, and cardiovascular complications. Intestinal microbiota can be modulated by changing one’s lifestyle but also by antibiotic, probiotic, prebiotic, and fecal transplantation. The purpose of this article is to highlight issues related to the involvement of microbiota and trimethylamine N-oxide in the pathogenesis of diabetes mellitus and cardiovascular disease. Better appreciation of the interactions between food intake and intestinal floral-mediated metabolism can provide clinical insights into the definition of individuals with diabetic risk and cardiometabolic disease as well as potential therapeutic targets for reducing the risk of progression of the disease.